Leveraging Intellectual Property Search Systems : A study on Trademark Portfolio Management for Portuguese and French Wineries - Correia Moreira, Mafalda Cristina (2024)
This thesis investigates the utilization of Intellectual Property (IP) Search Systems in managing trademark portfolios within the wine industries of Portugal and France. Given the large size and intense competition in the wine sector, effective trademark management is crucial for maintaining brand integrity and market differentiation. The study aims to explore the best practices in leveraging IP Search Systems to enhance competitive intelligence and strategic trademark management. Through a comparative analysis of Portuguese and French wineries, the research evaluates the Search Systems employed, identifies the benefits and limitations of these systems, and examines how key players in both countries manage their trademark portfolios. The findings highlight the significant differences and similarities in the countries’ trademark strategies, providing insights into the optimization of trademark Search Systems for improved trademark management in the wine industry. The study concludes with recommendations for addressing the limitations of current Search Systems to better support trademark portfolio management.